Intercropping of Pepper (Capsicum annuum L.) and Black Cumin (Nigella sativa L.) Optimize Crop Performance and System Productivity in Ethiopia: Systematic Review - Yohannes Gelaye (Cogent Food & Agriculture)
Intercropping is an essential farming system that combines multiple crop species simultaneously. In Ethiopia, Pepper and Black cumin are interplanted with various crops, influenced by diverse environmental and agronomic factors. This review examines the impact of intercropping Pepper and Black cumin on the performance of component crops and system productivity in Ethiopia. Farmers in tropical regions practice intercropping widely to reduce dependence on monoculture, manage risks from pests, diseases, and climate variability, and enhance resilience. By integrating Pepper and Black cumin with other crops, small‑scale farmers in developing countries like Ethiopia diversify crop production and improve yields. Most smallholder farmers in Ethiopia cultivate plots smaller than one hectare. The Land Equivalent Ratio is a key measure for evaluating intercropping efficiency. However, indices such as Relative Yield Total, Staple Land Equivalency Ratio, Area Time Equivalency Ratio, and Area Harvest Equivalency Ratio are also applied globally. These indices help assess the benefits of intercropping in terms of land use and time management. To maximize productivity, farmers must carefully select crops that balance resource competition, resist pests and diseases, and ensure yields with superior quality. Promoting sustainable intercropping practices can boost agricultural output and contribute to food security in Ethiopia and similar regions.